Possible mechanism by which zinc protects the testicular function of rats exposed to cigarette smoke - Sankako, Michele K. [UNESP]; Garcia, Patricia C. [UNESP]; Piffer, Renata C. [UNESP]; Dallaqua, Bruna [UNESP]; Damasceno, Débora Cristina [UNESP]; Pereira, Oduvaldo C. M. [UNESP] (Polish Acad Sciences Inst Pharmacology, 2012)
Background: The aim of this study was to evaluate the changes in testicular function of rats due to cigarette smoke exposure and the possible mechanism by which zinc protects against these alterations. Methods: Male Wistar rats (60 days old) were randomly divided into 3 groups: control (G1, n = 10); exposed to cigarette smoke (G2, n = 10; 20 cigarettes/day/9 weeks) and exposed to cigarette smoke and supplemented with zinc (G3, n = 8; 20 cigarettes/day/9 weeks; 20 mg/kg zinc chloride daily for 9 weeks, by gavage). After the treatment period, the animals were euthanized, and materials were collected for analyses. Results: G2 rats showed a reduction in body mass; impaired sperm concentration, motility, morphology and vitality; and increased malonaldehyde and thiol group levels and superoxide dismutase activity as compared to G1. Zinc prevented the reduction of sperm concentration and the excessive increase of lipid peroxidation and induced an increase in plasma testosterone levels, wet weight of testis and thiol group concentration. Conclusions: Exposure to cigarette smoke led to harmful effects on testicular function at least partially due to the exacerbation of oxidative stress. Supplementary zinc had an important modulator/protector effect on certain parameters. The mechanism of zinc protection can be through an increase of SH concentration. Thus, zinc supplementation may be a promising addition to conventional treatments for male infertility related to smoking.
Keywords: oxidative stress; rats; semen; smoking; spermatozoa; testis; zinc